+0  
 
0
240
1
avatar

If f(x) = -x³ + x² + x, find f(-2)

Guest Mar 20, 2017
 #1
avatar+7155 
+2

f(x) = -x³ + x² + x

 

To find f(-2), just replace every single " x " with " -2 ", then simplify.

f(-2) = -(-2)³ + (-2)² + (-2)

f(-2) = -(-8) + 4 + (-2)

f(-2) = 8 + 4 - 2

f(-2) = 10

hectictar  Mar 20, 2017

7 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.